Development of Business and Energy Module Based on Problem Based Learning - Endang Lovisia; Yuli Febrianti (Postgraduate, University of Mataram, 2025)
The problems of this research are results of observations at SMP Negeri Air Satan, it shows that science learning in schools has not been implemented in an integrated manner. One of the causes of the non-implementation of science learning is that science teachers, especially the material of effort and energy in junior high school, are not ready because there is no science teaching material on effort and energy. This research aims to 1) Design a module of Effort and Energy based on Problem Based Learning 2) Measure the feasibility of science modules based on Problem Based Learning in terms of validity, practicality and effectiveness. The method used is a research and development approach which is usually known as the R&D research method. The development design used is the 4D model development design. The results showed that the average of the analysis of the three validators, namely material, media and language experts, scored 26 in the good category. Analysis of student practicality in limited group trials obtained a score of 77% meeting practical criteria. The results of the calculation of the student practicality questionnaire in the large group trial obtained a score of 87.36%, meeting the criteria for being very practical. The increase in student learning outcomes was 0.61 with a moderate category.